The role of genetic testing in the prevention of acute aortic dissection. (29th August 2020) - Carino, Davide; Agostinelli, Andrea; Molardi, Alberto; Benassi, Filippo; Gherli, Tiziano; Nicolini, Francesco
Abstract: Although much has been learned about disease of the thoracic aorta, most diagnosis of thoracic aortic aneurysm (TAA) is still incidental. The importance of the genetic aspects in thoracic aortic disease is overwhelming, and today different mutations which cause TAA or alter its natural history have been discovered. Technological advance has made available testing which detects genetic mutations linked to TAA. This article analyses the genetic aspects of TAA and describes the possible role of genetic tests in the clinical setting in preventing devastating complications of TAA.